A bird's eye view of farm size and biodiversity: The ecological legacy of the iron curtain. Issue 4 (16th November 2021) - Noack, Frederik; Larsen, Ashley; Kamp, Johannes; Levers, Christian
Abstract: Agriculture is a major threat to global biodiversity. A common claim is that large‐scale agro‐industrial farming is mainly responsible for the biodiversity decline, while smaller family farms are more wildlife friendly. Here we leverage a natural experiment along the former inner German border to estimate the causal impact of farm size on biodiversity. We combine land cover data with bird diversity data to establish the mechanisms through which farm size affects bird diversity. Our main results show that the increase in farm size at the former inner German border reduces bird diversity by 15%. The results suggest further that the decline is the result of land cover simplification rather than land use intensification.